The Influence Of Leadership Style And Work Discipline On Employee Performance At PT. Elang Utama Jaya Putra South Tangerang - Mulyasaroh, Aprilia; Effendy, Aidil Amin (Transforma Jurnal Manajemen, 2025)
The study aims to determine the influence of leadership style and work discipline on employee performance ata PT Elang Utama Jaya Putra South Tangerang partially or simultancously. The method used is a quantitative method. The sampling technique used was saturated sampling using a sampling of 52 responden.Data collection techniques are through primary and secondary data. The data analysis technique used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis test using the Statistical Package for the Social Science (SPSS) version 26. The results of the study show that there is a positive influence between leadership style and partial employee performance. Where the simple linear regression equation Y= 9.450+0.736X1 means that it has a positive effect, the t-test is 6.780>Ttable 2.009, then Ha1 is accepted and Ho1 is rejected. There is a positive influence between work discipline and partial employee performance. Where the simple linear regression equation Y= 9.149+0.723X2 means that it has a positive effect, the t-test is 4.939>Ttable 2.009, then Ha2 is accepted and Ho2 is rejected. There is a positive influence between the variables of leadership style and work discipline on employee performance simultaneously where the multiple regression equation Y= 3.174+0.581X1+0.300X2 means that it has a positive effect, the multiple correlation test r= 0.717 is included in the category is quite strong, the determination coefficient is 49.4% and the rest is 50.6% which is influenced by other factors, the f test is Fcal 25.929>Ftable 3.19 means that it can be concluded that the variables of leadership style and work discipline have a significant effect on employee performance.